2010
DOI: 10.1108/14626001011068699
|View full text |Cite
|
Sign up to set email alerts
|

Influences on innovation in small Australian construction businesses

Abstract: PurposeThe purpose of this paper is to identify the major influences on innovation delivery in the context of small Australian construction businesses.Design/methodology/approachAn analysis was undertaken of peer‐reviewed journal articles published between 1998 and 2008. Historical background to the current circumstances was included by reference to influential government reports and to literature on the economic theory underpinning the concept of innovation.FindingsThe findings suggest that despite the recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Moulaert and Sekia (2003) talk about such theories as coming through the Marshallian "backdoor". In such circumstances, tacit and explicit knowledge are developed and exchanged (Hardie, 2010) to create regional advantage (Maskell et al, 1998). Gordon and McCann (2000) suggest these sociological and geographical themes have become somewhat entwined under the umbrella notion of 'innovative milieux'.…”
Section: Introductionmentioning
confidence: 99%
“…Moulaert and Sekia (2003) talk about such theories as coming through the Marshallian "backdoor". In such circumstances, tacit and explicit knowledge are developed and exchanged (Hardie, 2010) to create regional advantage (Maskell et al, 1998). Gordon and McCann (2000) suggest these sociological and geographical themes have become somewhat entwined under the umbrella notion of 'innovative milieux'.…”
Section: Introductionmentioning
confidence: 99%
“…As mostly observed in the industry, the risk is likely to be shifted to small contractors. Their poor long-term planning leaves them financially stranded in such cases [23]. Risk identification is a crucial step in decision making when an enterprise is uncertain about the probability of unforeseen risks [24].…”
Section: Risk Management In Constructionmentioning
confidence: 99%
“…Risk management awareness; coordination among project team members; risk management styles; effective use of tools and methods; enterprise strategic objectives; internal and external environment; less qualified risk professionals; client requirements and cooperative culture. Source: Chileshe and Kikwasi [23] As seen in the table, the critical challenges to adopting a conventional risk management approach are affected by the poor awareness of risk handling techniques, enterprise managers' lack of risk management, time constraints, inadequately trained risk personnel, and poor budget allocation for risk training and practice. If an enterprise fails to practice conventional risk management, there is little chance of integrating other risk management techniques.…”
Section: Tanzaniamentioning
confidence: 99%
“…However, many scholars reported that the characteristics of the construction industry worldwide, as well as Malaysia, are dominated by small-medium firms and, thus, it should be well sustained. Furthermore, Hardie (2010) along Hardie and Newell (2011) believe that if sufficient support and encouragement are provided to the small-medium construction businesses, they would be able to deliver a potentially significant contribution to the economic and environmental performance of the construction industry.…”
Section: Introductionmentioning
confidence: 99%